Quality of life after intra-arterial treatment for acute ischemic stroke in the MR CLEAN trial—Update. Issue 7 (October 2017) - Schreuders, Jennifer; van den Berg, Lucie A; Fransen, Puck SS; Berkhemer, Olvert A; Beumer, Debbie; Lingsma, Hester F; van Oostenbrugge, Robert J; van Zwam, Wim H; Majoie, Charles BLM; van der Lugt, Aad; de Kort, Paul LM; Roos, Yvo BWEM; et al.
Background: Health-related quality of life measured with the EuroQol Group 5-Dimension Self-Report Questionnaire was one of the secondary outcomes in the Multicenter Randomized Clinical trial of Endovascular treatment for Acute ischemic stroke in the Netherlands (MR CLEAN). We reported no statistically significant difference in EuroQol Group 5-Dimension Self-Report Questionnaire score between the intervention and control groups, but deaths were not included. Aims: Reanalyze the effect of intra-arterial treatment for large vessel occlusion in acute ischemic stroke patients on health-related quality of life in more detail. We now include patients who died during follow-up. Methods: The EuroQol Group 5-Dimension Self-Report Questionnaire questionnaires were obtained 90 days after treatment. We used the Dutch tariff to derive a utility index from the EuroQol Group 5-Dimension Self-Report Questionnaire score. Treatment effect was estimated with the Mann–Whitney U test and linear regression. The effect of treatment on the distribution of EuroQol Group 5-Dimension Self-Report Questionnaire dimension scores was assessed with ordinal logistic regression. Results: We obtained EuroQol Group 5-Dimension Self-Report Questionnaire scores from 457 (91.7%) of the 500 patients, including 108 who died before follow-up. Median EuroQol Group 5-Dimension Self-Report Questionnaire score in the intervention group was 0.57, and 0.39 in the control group (p = 0.03). Treatment effect estimated with linear regression was 0.07 (95%CI: −0.001 to 0.143). Treatment specifically affected EuroQol Group 5-Dimension Self-Report Questionnaire dimensions "mobility" (OR: 0.43, 95%CI: 0.29–0.66), "self-care" (OR: 0.60, 95%CI: 0.41–0.89), and "usual activities" (OR: 0.53, 95%CI: 0.36–0.79). Conclusion: Treatment had a limited effect on quality of life, as measured with the EuroQol Group 5-Dimension Self-Report Questionnaire. Nevertheless, patients with acute ischemic stroke caused by an intracranial occlusion in the anterior circulation, who had intra-arterial treatment, experience better health-related quality of life than patients without intra-arterial treatment. Trial Registration: URL:http://www.isrctn.com/ISRCTN10888758 Unique identifier: ISRCTN10888758